Reinforcement of in fractions and division arithmetic skills in primary school children through a serious educational game - Coronado Álvarez, Renato (2022)
While mathematics may be easy for some students, for others it can be a real torture. Through mathematics we can organize ourselves better and have much more logic and reasoning, as it is also the base knowledge for many professions. However, many people find it difficult and do not feel motivated to learn or reinforce it, mainly due to the traditional methodology, the difficulty of mathematics or the quality of education. On the other hand, technology and games can promote learning, becoming the best ally to enhance education. Moreover, in order to engage students in higher-order thinking, it is important to design game contexts and missions that allow them to deal with practical problems. For this reason, this article aims to support the process of reinforcement of learning fractions and divisions through an educational serious game available for web and mobile platforms, which incorporates continuous mechanics and the inclusion of reinforcement exercises of fractions and divisions. For the design of the game and interfaces, the heuristics proposed by Nielsen (1994), were applied and for the mechanics, the MDA framework was applied, which influenced the design of the levels together with the recommendations of a focus group. Subsequently, we will proceed to validate whether there were changes in the students’ performance by comparing groups, validate the usability in order to verify that the heuristics are correctly applied and, finally, measure the experience of the game in a small group of schoolchildren from 3rd grade onwards.